2021
DOI: 10.1002/cbic.202100304
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine NMR Spectroscopy Enables to Quantify the Affinity Between DNA and Proteins in Cell Lysate

Abstract: The determination of the binding affinity quantifying the interaction between proteins and nucleic acids is of crucial interest in biological and chemical research. Here, we have made use of site-specific fluorine labeling of the cold shock protein from Bacillus subtilis, BsCspB, enabling to directly monitor the interaction with single stranded DNA molecules in cell lysate. High-resolution 19 F NMR spectroscopy has been applied to exclusively report on resonance signals arising from the protein under study. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The concentration of cell lysate does not significantly modify the interaction between a ligand and its target protein [68] . However, increasing the concentration of cell lysate within CFS results in a monotonic increase in the thermodynamic stability of the Bacillus subtilis cold shock protein B ( Bs CspB).…”
Section: In Vivo Functions That Are Mostly Preserved In Lysa...mentioning
confidence: 99%
“…The concentration of cell lysate does not significantly modify the interaction between a ligand and its target protein [68] . However, increasing the concentration of cell lysate within CFS results in a monotonic increase in the thermodynamic stability of the Bacillus subtilis cold shock protein B ( Bs CspB).…”
Section: In Vivo Functions That Are Mostly Preserved In Lysa...mentioning
confidence: 99%
“…However, NMR studies in cellular extracts (bacterial, xenopus oocytes, mammalian) have demonstrated that it is also possible to obtain structural information on macromolecules, such as proteins and nucleic acids, in physiological conditions and they are easier to conduct than in-cell NMR ( Luchinat and Banci, 2022 ; Theillet and Luchinat, 2022 ). For example, NMR studies of nucleic acids in cell extract has been carried out to monitor the maturation of tRNAs in yeast extract ( Barraud et al, 2019 ) or to analyse ssDNA/protein interaction by 19 F labelling of the protein and NMR analysis in E. coli cell lysate ( Welte et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…NMR-active isotope 19 F nuclei with 100% natural abundance exhibit a wide chemical shift range (∼400 ppm), which is exquisitely sensitive to the electronic microenvironment . These merits make 19 F NMR incredibly useful in the fields of analytical chemistry and chemical biology, such as the analysis of a complex multicomponent mixture, quantification of hydrogen bonds, and the conformational investigation of proteins or nucleic acids. …”
Section: Introductionmentioning
confidence: 99%